La Gestión por procesos de la empresa VIPKARD de la ciudad de Riobamba y su incidencia en la productividad, periodo 2018-2019 - Cristian Dario, Yedra Muñoz (2021)
ABSTRACT The Management Model aimed at evaluating the productivity of the VIPKARD company constitutes a tool for making decisions efficiently and obtaining a competitive advantage by affecting the productivity levels of the company. This qualitative study was carried out with the participation of 16 clients and a survey composed of 30 items was designed and applied, of which 15 were related to management by processes based on categories and indicators composed of resource optimization (reduction of costs, less waste), efficiency (performance, productivity, competition); efficiency (meeting objectives, customer satisfaction). The other 15 items based on productivity were composed of resources (resource level); production (level of production); efficiency (quality level, product characteristics, performance). The data were processed using the SSPS version 22 program, through the calculation of frequency and levels of significance. With the results achieved, it can be deduced that there are statistically significant relationships between the variables management by processes and productivity. The reliability analysis of the items that make up each variable gives rise to a Cronbach's alpha coefficient for process management was 0.901 and 0.923 for productivity, respectively. This work through the management model that allowed to identify the key elements when measuring the fulfillment of the main objectives and continuous improvement, through the search for strategies; to achieve results in optimal productivity levels both in economic and financial terms as well as operational and satisfaction of all who make up this company. Keywords: management, productivity, processes, process management Reviewed by: Mgs. Marcela González Robalino English Professor c.c. 060301770